2006
DOI: 10.1007/s11414-006-9040-4
|View full text |Cite
|
Sign up to set email alerts
|

Nonkin Natural Mentors in the Lives of Older Youths in Foster Care

Abstract: This study explored the nonkin natural mentoring relationships among older youths in foster care. Three hundred thirty-nine youths nearing their exit from one state's alternative care system were interviewed. Those that reported the presence of a natural mentor, 62% (n=211), were subsequently asked about how they met their mentor, how long they have known their mentor, how frequently they have contact with their mentor, and the quality of the relationship. Seventy percent of the youth with mentors reported hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
2
15
1
Order By: Relevance
“…Interviews were conducted between December 2001 and May 2003. Two studies have been published on the natural mentoring relationships among 339 of these older youth who were interviewed at 18 years of age (See Munson & McMillen, 2008, 2009). Participants (n=189) in the present study are all youth that reported the presence of a natural mentor at 19 and answered the qualitative questions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interviews were conducted between December 2001 and May 2003. Two studies have been published on the natural mentoring relationships among 339 of these older youth who were interviewed at 18 years of age (See Munson & McMillen, 2008, 2009). Participants (n=189) in the present study are all youth that reported the presence of a natural mentor at 19 and answered the qualitative questions.…”
Section: Methodsmentioning
confidence: 99%
“…Foster care youth also report having connections beyond their families, with these youth reporting the presence of natural mentors at about the same rate as youth in the general population (Munson & McMillen, 2008; Ahrens, DuBois, Richardson, Fan & Lozano, 2008; Collins, Spencer, & Ward, in press). Beyond these accounts of prevalence, however, there has been little attention paid to the quality of the ties foster care youth form with natural mentors.…”
Section: Introductionmentioning
confidence: 99%
“…At 18, 62% (211) reported the presence of a natural mentor, with 70% reporting having known their natural mentor for over 1 year. Also, approximately half of those that nominated a natural mentor reported having met them through “formal” pathways, such as the mental health, education and child welfare systems, with another 46% reporting having met their mentor through family, friends or the neighborhood (Munson & McMillen, 2006). …”
Section: Methodsmentioning
confidence: 99%
“…This programming has been developed based on the notion that by using a cognitive theory instructional model designed to teach older foster youth certain skills considered related to self-sufficiency, they will be ready to successfully transition to adulthood and live independently. Alternatively, mentoring is grounded in Relational-Cultural Theory (Munson & McMillen, 2008), which posits that development occurs through involvement in growth-fostering relationships that provide authenticity, engagement, and empowerment, which in turn promote psychological health and well-being (Jordan et al, 1991).…”
Section: Implications For Practice Policy and Researchmentioning
confidence: 99%